Variation of technological properties of field natural rubber lattices from Hevea brasiliensis clones and natural rubber-based compounds (2017)
Natural rubber (NR) is a widely used biopolymer, but the variability of its properties is a great disadvantage. In this work, variation during a 6-month period of total solids (TSC), dry rubber (DRC), ash, volatile-matter, and nitrogen content of field natural rubber (NR) lattices and mechanical properties of NR solid sheets-based compounds was studied. NR samples were collected from IAN 710, IAN 873 and FX 3864 clones of Hevea brasiliensis at a plantation within the state of Antioquia, Colombia. Rainfall, environmental temperature, relative humidity, and sunlight hours were daily registered. NR sheets-based compounds were manufactured and their rheometric and mechanical properties were measured. Significant variations (p0.05) among clones and tappings for most of the measured properties were found. Leaf senescence was the phenological stage that presented the greatest influence on NR properties. Some recommendations to control the variation of properties of raw NR during manufacturing of rubber goods were stated.